Analyzing ChatGPT’s Impact on Graduates’ Communication, Collaboration, and Logical Thinking Skills Using an Extended Technology Acceptance Model - Hasri, Raja Alan; Miranda, Eka (Informatika, Universitas Jenderal Soedirman, 2025)
The rapid rise of ChatGPT in Indonesia—now the third-highest user base worldwide—raises questions about its impact on essential soft skills for new graduates. Recent evidence warns that while ChatGPT supports academic and professional tasks, it may also reduce critical thinking, collaboration, and communication if not properly guided. This study aims to evaluate how ChatGPT usage affects communication, collaboration, and logical thinking skills among recent graduates in Jabodetabek. A cross-sectional survey of 384 respondents was conducted, and data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The modified Technology Acceptance Model (TAM) demonstrated strong explanatory power, with R² values of 0.830 for Behavioral Intention, 0.699 for Actual Use, and 0.651 for Attitude Toward Use. Hypothesis testing confirmed significant effects, including Perceived Ease of Use on Perceived Usefulness (β = 0.946; t = 172.023; p < 0.001) and Behavioral Intention on Actual Use (β = 0.836; t = 50.416; p < 0.001). Positive attitudes toward ChatGPT were strongly associated with enhanced teamwork, communication, and logical reasoning. This study contributes to the discourse on digital literacy and educational technology in Southeast Asia, demonstrating that ChatGPT can strengthen graduate employability when integrated with proper guidance and ethical use. The findings provide practical implications for computer science and education fields, offering a framework for balancing AI adoption with the preservation of critical human skills.